ASSESSMENT OF IN VITRO STUDIES OF [131I]I-LABELED DEDEYFELV PEPTIDE AS PROSPECTIVE BIOMARKER FOR GLIOBLASTOMA - Fernanda Paiva Augusto Rodrigues; Júlia Calviello Giordano; Danielle Vieira Sobral; Ana Cláudia Camargo Miranda; Leonardo Lima Fuscaldi; Marycel Figols de Barboza; João Luiz Vitorino Araújo; Luciana Malavolta (Hematology, Transfusion and Cell Therapy, 2024)
Introduction/Justification: Glioblastomas (GBM) constitute the most prevalent malignant primary tumor in adults and rank as the third most frequent tumors in the central nervous system. The predominant alteration observed in GBM is associated with the tyrosine-kinase pathway, facilitating the connection of growth factors to receptors. Notably, in GBM the overexpression of the epidermal growth factor receptor (EGFr) has opened new treatment perspectives, including molecular targeted therapies, with peptides taking center stage. Recently, radiolabeled peptides with high affinity for EGFr have been employed as potential agents for molecular imaging or targeted radionuclide therapy as anti-tumor agents. Objectives: The aim of the study was to assess the interaction between [131I]I-DEDEYFELV peptide and human glioblastoma cells (U-87 MG), as well as with GBM tissue. Materiais e Métodos: The DEDEYFELV peptide was synthesized through solid-phase peptide synthesis using the Fmoc/tBut strategy. Peptide cleavage from the resin was performed using a mixture containing a high concentration of trifluoroacetic acid (reagent K). Subsequently, the peptides underwent a characterization and purification process employing high performance liquid chromatography (HPLC) and mass spectrometry. The U-87 MG cell line was cultured in supplemented DMEM F-12 medium at 37°C and 5% CO2 until reaching 90% confluence. The neoplastic tissue was surgically removed, histopathologically analyzed, and preserved at -80°C, with its homogenate prepared using PBS buffer (pH 7.4) at 10 mg of tissue/mL. The DEDEYFELV (20 nmol) was radiolabeled with the [131I]NaI radionuclide (18.5 MBq), using the chloramine-T method. The radiochemical yield of the [131I]I-DEDEYFELV was carried out by on Whatmann 3MM strips using 95% MeOH / 5% H2O as eluent. Binding and internalization studies of the [131I]I-DEDEYFELV with tumorigenic cells (U-87 MG) and neoplastic tissue homogenate were evaluated at 1 and 3 h of incubation and measured in an automatic gamma counter. Results: The DEDEYFELV peptide was efficiently synthesized and characterized, with yield of approximately 92%. Chromatographic analyzes obtained by HPLC confirmed that the entire synthesis, cleavage, and characterization process of peptides were performed efficiently, as evidenced by the presence of only a single peak corresponding to the synthesized peptide with molecular mass of 1158.18 g/mol. The radiolabeling process was successful obtained with radiochemical yield > 95%. Binding and internalization studies of the [131I]I-DEDEYFELV conducted with U-87 MG cells showed values of 15.90% ± 1.67 and 54.57% ± 0.90 (n = 5), respectively. On the other hand, the binding percentage of 12.45% ± 0.90 and internalization of 28.41% ± 3.15 (n = 5) were achieved with neoplastic tissue homogenate within a 3-hour period. Conclusion: The proposed peptide was efficiently synthesized, and radiolabeling studies with [131I]NaI exhibited a high radiochemical yield. Binding and internalization studies revealed that the [131I]I-DEDEYFELV peptide has a good affinity for both U-87 MG and neoplastic tissue homogenate, demonstrating higher internalization of [131I]I-DEDEYFELV in human glioblastoma cells. Nevertheless, it is crucial to emphasize that additional in vivo investigations are necessary.